Entropy generation on MHD slip flow over a stretching cylinder with heat generation/absorption - Jain, Shalini; Bohra, Shweta (Zielona Góra: Uniwersytet Zielonogórski)
In the present study, we have investigated entropy generation on a magnetohydrodynamic fluid flow and heat transfer over a stretching cylinder with a porous medium in slip flow regime. A uniform heat source and radiation is also considered. Similarity transformation has been applied for making an ordinary differential equation from nonlinear governing partial differential equations.
Keywords: magnetohydrodynamics; heat generation; slip; entropy